Repetitive Imaging following Minimally Invasive Repair of Pectus Excavatum Is Unnecessary - Sola, Richard; Yu, Yangyang R.; Friske, Tyler C.; Jamal, Abdur R.; Rosenfeld, Eric H.; Mazziotti, Mark V.; Peter, Shawn D. St.; Shah, Sohail R. (European Journal of Pediatric Surgery, 2019)
Introduction The objective of this study was to evaluate the necessity of repeat imaging after an initial chest radiograph (CXR) following minimally invasive repair of pectus excavatum (MIRPE).Materials and Methods A retrospective review was performed on patients who underwent MIRPE from January 2012 to July 2016 at two academic children's hospitals. Data collected included demographics, severity of pectus defect (Haller index [HI]), utilization of CXRs, outpatient follow-up, and clinical outcomes.Results A total of 360 patients (171 at Hospital 1 and 189 at Hospital 2) underwent MIRPE. Median age was 15.6 years and 84% were males. The median HI was 4.0. Median postoperative hospital length of stay was 4.2 days and median time to bar removal was 34 months. There was significant variation in postoperative imaging between the hospitals, including frequency of immediate postoperative CXR, total number of CXRs during hospitalization, and number of postoperative outpatient CXRs prior to bar removal. However, there was no significant difference in outcomes between the hospitals, including postoperative pneumothorax, postoperative chest tube placement, and complications.Conclusion These data suggest that increased repetitive imaging after an initial postoperative CXR does not affect clinical outcomes and may not be necessary after MIRPE.
Keywords: pectus excavatum; minimally invasive repair of pectus excavatum; resource utilization; children